The Role of Learning Models in Numeracy Ability and Its Relationship With Self-Efficacy: A Systematic Literature Review - Afifah; Sujana, Atep; Supriatna, Encep; Salim, Herli (International Conference on Elementary Education, 2025)
This study aims to describe numeracy literacy skills through learning models and their relationship with self-efficacy skills. The research method used is a Systematic Literature Review (SLR) which includes 3 stages, namely planning, conducting, and reporting. The data collection process was carried out by identifying articles relevant to the research topic based on predetermined criteria. This study examined 20 articles based on search results from the Google Scholar database with the help of the Publish Or Perish software. The data synthesis in this study was then presented in data tables and reinforced with narrative forms. The results of this study show that the improvement of numeracy literacy at the elementary school level for the period 2020-2025 is predominantly achieved by implementing the problem-based learning (PBL) model. On the other hand, students' self-efficacy also has an influence on learning success. Furthermore, students' numeracy literacy has a positive correlation with self efficacy, characterized by the higher the students' self efficacy, the higher their numeracy literacy.